Oxidative Stress From Exposure to the Underground Space Environment - Yu, Hongbiao; Gao, Yijie; Zhou, Rong (Frontiers in Public Health, 2020)
There are a growing number of people entering underground spaces. However, underground spaces have unique environmental characteristics, and little is known about their effects on human health. It is crucial to elucidate the effects of the underground space environment on the health of humans and other organisms. This paper reviews the effects of hypoxia, toxic atmospheric particles, and low background radiation in the underground space environment on living organisms from the perspective of oxidative stress. Most studies have revealed that living organisms maintained in underground space environments exhibit obvious oxidative stress, which manifests as changes in oxidants, antioxidant enzyme activity, genetic damage, and even disease status. However, there are few relevant studies, and the pathophysiological mechanisms have not been fully elucidated. There remains an urgent need to focus on the biological effects of other underground environmental factors on humans and other organisms as well as the underlying mechanisms. In addition, based on biological research, exploring means to protect humans and living organisms in underground environments is also essential.